Synthesis and in Vitro Cytotoxic Activity of Some New Colchicine Analogues - Sen Wang, Jian; Wang, Bo; Yu Li, Hong; Hong Shen, Li; Zhang, Xu; Jie Liu, Li (Asian Journal of Chemistry, 2013)
A series of new colchicine analogues (6a-f, 8a-b) were synthesized by coupling nitrates with C-7 and replacement of the 10-methoxy with N(CH3)2 in order to determine their cytotoxic activity. The compounds were synthesized in good yield and the structures of all newly synthesized compounds were established on the basis of their IR, 1H NMR and elemental analysis. The synthesized compounds were tested in vitro antitumor activity against four human cancer cell lines by MTT assay. It was found that many of the derivatives displayed significant activity, particularly, compound 6c showed more potent cytotoxic activities than colchicine.